Policy-oriented pathways for decoupling economic growth from carbon emissions in Southwest China: a GDIM analysis of multi-driver dynamics and regional heterogeneity - Youwei, Wan; Yaru, Xu; Binhui, Pan; Xinfa, Tang (Frontiers in Environmental Science, 2025)
Southwest China, an ecologically fragile region, faces acute dual challenges of sustaining economic growth while achieving carbon mitigation targets. This study employs the Generalized Divisia Index Method (GDIM) to quantify interactions among eight drivers of CO2 emissions in Yunnan, Guizhou, and Sichuan (2012–2023). Results reveal that GRP growth remains the dominant driver (32%–39% contribution) but with declining influence, signaling partial decoupling. Crucially, output carbon intensity (CO2/GDP) emerges as the strongest inhibitor (−26 to −30%), primarily due to industrial upgrading and clean energy transitions. Notable regional divergence is observed: per capita emissions rise in coal-dependent Guizhou but decline in hydropower-rich Yunnan and Sichuan. We propose province-specific pathways: (1) optimizing the energy structure and increasing the proportion of clean electricity; (2) Strengthen energy efficiency improvement in key industries; (3) Innovative regional collaborative emission reduction mechanism; (4) Promote low-carbon transformation of daily consumption; (5) Strengthen data foundation and capacity building. These findings provide actionable insights for low-carbon governance in developing regions with high ecological vulnerability.